2018
DOI: 10.1523/jneurosci.3276-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Transporter OATP2A1/SLCO2A1 Is Essential for Body Temperature Regulation during Fever

Abstract: Prostaglandin E (PGE) in the hypothalamus is a principal mediator of the febrile response. However, the role of organic anion transporting polypeptide 2A1 (OATP2A1/), a prostaglandin transporter, in facilitating this response is unknown. Here, we investigated the effect of deficiency on the body core temperature (Tc) and on the PGE concentration in hypothalamus interstitial fluid () and CSF () of lipopolysaccharide (LPS; 100 μg/kg, i.p.)-treated mice of both sexes. mice did not develop a febrile response. was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 51 publications
2
19
0
1
Order By: Relevance
“…Inhibiting the fatty acid desaturase SCD or its yeast ortholog OLE1 reduces levels of oleic acid and rescues α-synuclein toxicity in model organisms (Fanning et al, 2018;Vincent et al, 2018). Slco2a1 is a prostaglandin receptor expressed on microglia and endothelial cells that may play a role in neuroinflammation (Nakamura et al, 2018 [Deng, Xiu, & Jankovic, 2015]).…”
Section: Cg5278mentioning
confidence: 99%
“…Inhibiting the fatty acid desaturase SCD or its yeast ortholog OLE1 reduces levels of oleic acid and rescues α-synuclein toxicity in model organisms (Fanning et al, 2018;Vincent et al, 2018). Slco2a1 is a prostaglandin receptor expressed on microglia and endothelial cells that may play a role in neuroinflammation (Nakamura et al, 2018 [Deng, Xiu, & Jankovic, 2015]).…”
Section: Cg5278mentioning
confidence: 99%
“…RT-PCR confirmed mRNA expression of rat Oatp2a1 in brain capillary-rich fraction as well as whole brain. 27) Our laboratory reported Oatp2a1 immunoreactivity in mouse brain capillaries, 28) and Oatp2a1 was immunolocalized predominantly 40) Br, 39,46) Eye, 46,99) Ki and Li 39)…”
Section: At the Blood-brain Barriermentioning
confidence: 93%
“…Taogoshi et al reported that PGE 1 transport across the BBB is inhibited in the presence of bromocresol green, digoxin, or taurocholate by in situ rat brain perfusion technique. 27) Bromocresol green is a well-known inhibitor of OATP2A1. RT-PCR confirmed mRNA expression of rat Oatp2a1 in brain capillary-rich fraction as well as whole brain.…”
Section: At the Blood-brain Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Lysozyme (Lys) M-cre mice and Villin (V)-cre mice were obtained from RIKEN Bioresource Centre (RRID:IMSR_ RBRC02302) and Jackson laboratory (B6.Cg-Tg(Vil1-cre)1000Gum/J), respectively. Slco2a1 fl/fl mice were crossed with LysM-cre mice and V-cre mice to generate mice with specific Slco2a1 deletion in macrophages (Slco2a1 ΔMP ) 48 and intestinal epithelial cells (Slco2a1 ΔIEC ). Sex-and age-matched WT mice (C57BL/6), obtained from Charles River Japan Inc. (Atsugi, Japan), and sex-and age-matched littermate LysM-cre − ;V-cre − ;Slco2a1 fl/fl mice were used as controls for Slco2a1 −/− mice and Slco2a1 ΔMP Slco2a1 ΔIEC mice, respectively.…”
Section: Methodsmentioning
confidence: 99%